Management of Facilities and Infrastructure at SMP Muhammadiyah Jirak - Alfaizah, Iffah Marta; Harapan, Edy; Tahrun (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
Regarding the implementation of school-based management, one of which is infrastructure management. This researcher took the title, namely, Management of Facilities and Infrastructure at SMP Muhammadiyah Jirak with the sub-focus is planning, procurement, utilization, maintenance, person in charge and elimination. In this study, researchers used a qualitative method with a qualitative naturalistic approach. The naturalistic approach shows that the implementation of this research is indeed natural, as it is and is not manipulated by circumstances and conditions. In the data collection method, the writer uses techniques such as observation, interview and documentation. The results showed that the planning of infrastructure in SMP Muhammadi yah Jirak runs withgood. In addition, the planning stage is also carried out from submitting needs, then analyzing. Procurement of infrastructure at SMP Muhammadiyah Jirak always tries to do with the planning that has been made. In terms of the provision of infrastructure, it has also been carried out in accordance with the plans that have been made. In terms of the provision of infrastructure, it is not carried out by one or two parties, but involves various elements to avoid misuse in the provision of educational facilities. Utilization of facilities and infrastructure at SMP Muhammadiyah Jirak is by having rules and schedules for the use of facilities and infrastructure. Maintenance and accountability for facilities and infrastructure at SMP Muhammadiyah Jirak are carried out by all residents, including officers, school principals, teachers, administrative staff and other students. The elimination of facilities and infrastructure at SMP Muhammadiyah Jirak is carried out by the school by selecting goods and after that it will be reported to the KPKNL and will be carried out a sale or auction.